Comparative investigation of the optical spectroscopic and thermal effect in Nd3+-doped nanoparticles. Issue 21 (15th May 2019) - Wang, Shuai; Shen, Bin; Wei, Han-Lin; Liu, Zixiao; Chen, Zhigang; Zhang, Yong; Su, Yan; Zhang, Jun-Zheng; Wang, Haifang; Su, Qianqian
Abstract : The factors influencing upconversion luminescence, the energy transfer mechanism and their thermal effect in Nd 3+ -doped nanoparticles were comprehensively investigated. Abstract : Nd 3+ -doped nanoparticles involving 808 nm excitation hold great promise in various biomedical applications, such as bioimaging, biodetection, theranostics and optogenetics. Here we present the synthesis and characterization of core–multishell Nd 3+ -doped nanoparticles displaying excellent optical properties. We systematically studied the influence of doping concentration, nanostructure design, excitation wavelength and size effect on the upconversion luminescence of Nd 3+ -doped nanoparticles. Remarkably, the emission intensity of optimized nanoparticles with 808 nm excitation is three times higher than the emission intensity of those with 980 nm excitation. Surprisingly, the optical profiles of Nd 3+ -doped nanoparticles strongly depend on the excitation wavelengths. The dominant effect responsible for the emission intensity difference and the energy transfer mechanism upon different excitation wavelengths are investigated. Interestingly, the heavily Nd 3+ -doped nanoparticles not only display efficient upconversion luminescence, but also are able to convert the excitation source to heat under a single 808 nm excitation source. Importantly, these efforts will lead to Nd 3+ -doped nanoparticles with unprecedented optical and thermal properties that will have broad utility in fundamental research and technological applications.